Di (2‐ethylhexyl) phthalate targets the thioredoxin system and the oxidative branch of the pentose phosphate pathway in liver of Balb/c mice. Issue 1 (5th September 2019) - Amara, Ines; Timoumi, Rim; Annabi, Emna; Di Rosa, Gabriele; Scuto, Maria; Najjar, Mohamed F.; Calabrese, Vittorio; Abid‐Essefi, Salwa
Abstract: Di (2‐ethylhexyl) phthalate (DEHP) is a plasticizer that gives flexibility to various polyvinyl chloride products. It is a pollutant easily released into the environment and can cause many adverse effects to living organisms including hepatotoxicity. The thioredoxin system is a determining factor in the redox balance maintaining in the liver, which is a vulnerable tissue of reactive oxygen species overproduction because of its high energy needs. In order to determine if the thioredoxin system is a target in the development of DEHP hepatotoxicity, Balb/c mice were administered with DEHP intraperitoneally daily for 30 days. Results demonstrated that after DEHP exposure, biochemical profile changes were observed. This phthalate causes oxidative damage through the induction of lipid peroxydation as well as the increase of superoxide dismutase and catalase activities. As new evidence provided in this study, we demonstrated that the DEHP affected the thioredoxin system by altering the expression and the activity of thioredoxin (Trx) and thioredoxin Reductase (TrxR1). The two enzyme activities of the oxidative phase of the pentose phosphate pathway: Glucose‐6‐phosphate dehydrogenase and 6‐Phosphogluconate dehydrogenase were also affected by this phthalate. This leads to a decrease in the level of nicotinamide adenine dinucleotide phosphate used by the TrxR1 to maintain the regeneration of the reduced Trx. We also demonstrated that such effects can be responsible of DEHP‐induced DNA damage.